The phenomenon of prosumption in the digital transformation time - Wioletta Wereda; Florina Pînzaru (Nowoczesne Systemy Zarządzania, 2023)
The fusion of cutting-edge information technology and manufacturing, like cloud computing, the Internet of Things, big data fosters greater consumer involvement and engagement throughout the entire product life cycle. A shared vision for socially responsible, personalized, service-driven, smart, sustainable, and eco-friendly development is a global priority. The rapid progress of the „Internet +” and „intelligence +” scientific and technological revolution blurs the lines of various media channels, establishing an evolved environment that encourages expression, communication, creation, and sharing. This revolution launched the advent of prosumption, allowing consumers to take part in the production process via an „open + continuous” model that eclipses older, traditional media. This article endeavors to showcase the concept of prosumption during the era of digital transformation. Exploring recent prosumption case studies in enterprises, this article also utilized theoretical research methods. In addition to analyzing relevant literature through analytical-synthetic analysis, the study employed abstraction to focus on crucial elements for analysis. Furthermore, generalization and inference were utilized to draw conclusions from the findings. It should be stated as the main hypothesis that the prosumption has a great importance in the digital world. This article explores the notion of prosumption in the context of digital transformation. It’s important to note that digital transformation has revolutionized all aspects of businesses, especially the use of social media.